Hazard Identification Risk Assessment Kegiatan Praktek Structural Fire Pada Program Studi Pertolongan Kecelakaan - Tri Saputra, Surya; Supri (Faculty of Engineering, Universitas Serambi Mekkah, 2026)
Structural Fire Practice is a firefighting training activity in buildings carried out to equip students with technical skills in dealing with fire incidents in buildings or airport facilities. The risk to physical safety, health, and equipment damage is very high if hazard identification and risk management are not carried out systematically. The purpose of this study is to identify hazards and assess potential risks and provide mitigation so that these risks do not cause more severe consequences. This study was conducted using the Hazard Identification and Risk Assessment (HIRA) approach. The results of the study showed that there were 31 potential hazards covering human, equipment, environmental, and work procedure aspects. The results of the risk assessment showed that four potential hazards were in the intolerable category, namely: SCBA compressors that are not properly maintained, hoses that do not meet standards, manual fuel injection, and backdraft or flashover conditions. Mitigation measures implemented include increased supervision of equipment maintenance, the use of thermal imaging cameras, the implementation of SOPs, and safety training and briefings. The implementation of HIRA in training activities provides significant benefits in increasing safety awareness and reducing the potential for accidents in aviation education environments.